Adaptations of the Marsupial Newborn: Birth as an Extreme Environment. Issue 2 (7th January 2019) - Smith, Kathleen K.; Keyte, Anna L.
ABSTRACT: At birth a mammalian neonate enters an extreme environment compared to the intrauterine environment in which it has grown. This transition may be particularly extreme in marsupials because they are born at an exceedingly altricial state, after an exceptionally short gestation. Their stage of development must be considered embryonic by almost any criteria. Yet at this very early stage of development marsupials must travel to the teat, attach and suckle, and have basic functioning of all major physiological systems. In this article, we review the adaptations of the marsupial neonate for survival at an embryonic state, showing that the neonate exhibits a mosaic of accelerations and delays of various tissues and organs as well as several special adaptations to produce the functioning newborn. We then discuss the development of the craniofacial region, the body axis and limbs in order to detail some of the major changes to development leading to this uniquely configured neonate. We show that marsupial development arises out of a variety of heterochronies (changes in relative timing of events) and heterotopies (changes in location of specific developmental events) at the genetic, cellular and organ level. We argue that these data support hypotheses that many of the specific patterns seen in marsupial development arise from the basic constraint of embryonic energetic and tissue resources. Finally ideas on the evolutionary context of the marsupial developmental strategy are briefly reviewed. Anat Rec, 2019. © 2018 Wiley Periodicals, Inc. Anat Rec, 303:235–249, 2020. © 2018 American Association for Anatomy